2007
DOI: 10.2967/jnumed.107.042093
|View full text |Cite
|
Sign up to set email alerts
|

Early 18F-FDG PET for Prediction of Prognosis in Patients with Diffuse Large B-Cell Lymphoma: SUV-Based Assessment Versus Visual Analysis

Abstract: The purpose of this study was to assess the prognostic value of early 18 F-FDG PET using standardized uptake value (SUV) compared with visual analysis in patients with diffuse large B-cell lymphoma (DLBCL). Methods: Ninety-two patients with newly diagnosed DLBCL underwent 18 F-FDG PET prospectively before and after 2 cycles of chemotherapy (at midtherapy). Maximum SUV (SUVmax) and mean SUV (SUVmean) normalized to body weight and body surface area, as well as tumor-to-normal ratios, were computed on the most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
277
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(294 citation statements)
references
References 25 publications
(27 reference statements)
12
277
2
3
Order By: Relevance
“…Assessments during treatment or in clinical trials, however, may require quantification. [8][9][10] This is often challenging because cutoff levels of SUV to determine response to therapy are likely to depend on the tumor type and treatment administered and therefore need to be evaluated in prospective clinical trials. With the demonstration of the prognostic value of interim FDG-PET in classic Hodgkin lymphoma, different trials have now been initiated to use this information to direct individual treatment.…”
Section: Interpretation Of Pet Scansmentioning
confidence: 99%
“…Assessments during treatment or in clinical trials, however, may require quantification. [8][9][10] This is often challenging because cutoff levels of SUV to determine response to therapy are likely to depend on the tumor type and treatment administered and therefore need to be evaluated in prospective clinical trials. With the demonstration of the prognostic value of interim FDG-PET in classic Hodgkin lymphoma, different trials have now been initiated to use this information to direct individual treatment.…”
Section: Interpretation Of Pet Scansmentioning
confidence: 99%
“…[1][2][3][4] In particular, several studies that have evaluated the role of PET as a prognostic tool during chemotherapy have reported its ability to predict outcomes in aggressive NHL. [5][6][7][8][9][10][11] In force of the pivotal role played by PET in staging, restaging, and response evaluation, the International Workshop Criteria for malignant lymphoma 12 have been revised to incorporate the PET data in NHL outcome assessment, but only at the end of therapy.…”
mentioning
confidence: 99%
“…Recent reports of PET evaluation have demonstrated a greater degree of accuracy in early response assessment compared with computed tomography. [5][6][7][8][9][10][11] However, the benefit of midtreatment (or interim) PET evaluation in aggressive NHL is still a matter of debate, 24 and a meta-analysis conducted by Terasawa et al 3 indicated that interim PET has unproven reliability in routine clinical practice.…”
mentioning
confidence: 99%
“…or average SUV (32). This approach takes a little more time if multiple lesions are present but is highly reproducible and superior to visual analysis in specific tumors such as recently shown in lymphoma patients (33). More sophisticated and time-consuming measurements like total lesion glycolysis (TLG) promise to be more exactly to determine the tumor burdon because size and FDG-uptake of all lesions are assessed.…”
Section: Fdg-pet/ct Is Increasingly Used For Therapy Assessment Of DImentioning
confidence: 99%